An Impact of COVID-19 Pandemic on The Motivation and Psychological Well Being of Dermatology Residents - Mashhood, Asher Ahmed; Shahzadi, Shazia (Pakistan Armed Forces Medical Journal, 2022)
Objective: To analyze the motivation and psychological well-being to perform duties during the COVID-19 pandemic among the dermatology residents.Study Design: Cross-sectional survey.Place and Duration of Study: Dermatology Department, Combined Military Hospital, Rawalpindi, from Mar to Sep 2020.Methodology: A total of 155 dermatology residents were included in the study. Health care provider motivation scale (HCPMS) was used through online Google Doc due to lockdown. Secondary data was also generated from Google scholar, newspapers, journals, reports and the literature review.Results: We analyzed the impact of COVID-19 on motivation and psychological well-being. The result showed that the COVID-19 pandemic has an adverse effect on motivation due to anxiety (31%), stress (23%) and depression (27%) among dermatology residents. There was statistically significant relationship between decreased motivation and increased stress levels and depression among dermatology residents performing COVID-19 duties (p